Strategi Berkompetisi Pemasaran Mobil PT. Alifindo Sentral Batam - Sujono, Imam (Zona Manajerial: Program Studi Manajemen (S1), 2023)
The re-used car marketing business in Batam City is very tight. Many dealers and agents offer various car brands with attractiveness in terms of service, purchasing methods, promotions and other attractive packages. One dealer that has been around for quite a long time is PT Alfindo Sentral Mobil Batam. This company must be able to exist amidst intense competition. The main policies implemented by this dealer are in terms of service, promotions and prices. These three things have a big influence on customers' interests and decisions and have implications for car sales. The aim of this research is to find out how service, promotion and price influence car sales at PT Alfindo Sentral Mobil Batam. The research results show that service, promotion and price have a significant effect on car sales.